Prefabricated Corbel Keyway Hollow Column Inspection Pit for Urban Rail Transit Inspection Depot - LIU Guan; ZHAO Hai; ZHAI Beibei; ZHANG Guangming (Chengshi guidao jiaotong yanjiu)
［Objective］ The existing column inspection pit track bed of the urban rail transit train inspection depot has various disadvantages such as low construction efficiency, large cross-sectional size, and large embedded parts number. In this regard, it is necessary to propose a new type of prefabricated corbel keyway column (hereinafter abbreviated as PCKC) inspection tunnel bed. ［Method］ The structural composition and design of the prefabricated column and cast-in-place track bed of the new PCKC inspection pit is introduced. A static finite element model of the new PCKC inspection pit track bed is established to calculate its stress distribution. The main steps and inspection requirements for manufacturing PCKC are summarized. The bending performance of prefabricated columns is verified through field tests. Compared with ordinary column inspection pit track beds, the advantages of the new PCKC inspection pit track bed are analyzed. ［Result & Conclusion］ Compared with the traditional cast-in-place rectangular cross-section column, the PCKC reduces by 25% in self-weight; the corbel configuration improves the applicability of various fasteners and enhances the lateral stability; the keyway enhances the connection between the column and the track bed. The static model analysis and anti-bending test results show that the structural strength of the prefabricated column meets the design requirements. Compared with the cast-in-place column inspection track bed, the new PCKC inspection track bed has a beautiful appearance, reliable quality, no maintenance, equivalent steel bar consumption, and reduced concrete consumption. Although the single-line cost increases by about 250 000 yuan/km, the construction speed per working face increases by 75 m/d, reducing the number of workers/per working face by about 35%.